Luminescent Oxygen Sensor with Self-Sterilization Properties Based on Platinum(II)octaethylporphyrin in Polymeric Nanofibers - Ludačka, Pavel; Liška, Vojtěch; Sýkora, Jan; Kubát, Pavel; Mosinger, Jiří (ACS materials Au, 2025)
Optical sensors based on the quenching of the luminescence of platinum(II)octaethylporphyrin (PtOEP) encapsulated in nanofiber polymeric membranes were prepared by electrospinning. The samples were characterized using scanning electron microscopy, confocal luminescence microscopy, absorption spectroscopy, and steady-state and time-resolved luminescence techniques. The properties of the sensors were changed by the selection of different polymeric membranes using polycaprolactone, polystyrene, polyurethane Tecophilic, and poly(vinylidene fluoride-co-hexafluoropropylene) polymers. Among them, biodegradable and biocompatible sensors prepared from polycaprolactone with a high oxygen diffusion coefficient exhibited a fast response time (0.37 s), recovery time (0.58 s), high sensitivity (maximum I 0 /I ratio = 52), reversible luminescent response, and linear Stern-Volmer quenching over the whole range of oxygen contents in both the gas atmosphere and aqueous media. Moreover, the proposed sensors exhibited high antibacterial properties, resulting in self-sterilization character of the membrane surface due to the photogeneration of singlet oxygen. This dual character can find application in the biomedical field, where both properties (oxygen sensing and self-sterilization) can be acquired from the same material.